A positive electrode sheet and its preparation method and application
By reasonably combining lithium iron phosphate particles with different particle sizes and compaction density, the problem of poor storage performance of lithium-ion batteries under high temperature conditions is solved, and efficient storage and safety improvement of the battery is achieved.
Patent Information
- Application Number
- CN202210885514.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-26
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-07-26
AI Technical Summary
Existing lithium-ion batteries have poor storage performance under high temperature conditions, and nano-sized positive electrode active materials will react side-effect with the electrolyte, affecting the storage life and safety of the battery.
By reasonably combining lithium iron phosphate particles with different particle sizes and compaction density, the relationship between the median particle size and compaction density of the positive electrode active material is designed to form a battery with excellent rate performance and long storage life.
It significantly improves the storage performance of lithium-ion batteries under high temperature conditions, extends the storage life of the battery, and improves safety.
Smart Images

Figure GDA0005258364600000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium-ion batteries and relates to a positive electrode sheet and a preparation method and application thereof. Background Art
[0002] As the power source of new energy vehicles, lithium-ion batteries are mainly composed of four basic elements: positive electrode active materials, negative electrode active materials, electrolytes and separators. According to the different positive electrode active materials, lithium-ion batteries are mainly divided into lithium cobalt oxide (LiCoO2) batteries, lithium manganese oxide (LiMn2O4) batteries, lithium nickel oxide (LiNiO2) batteries, ternary (Li(NiCoMn)O2) batteries, lithium iron phosphate (LiFePO4) batteries, etc. Lithium cobalt oxide materials contain highly toxic cobalt elements and are expensive, making it difficult to ensure safety when making large power batteries. The material of lithium manganese oxide itself is not very stable and is easy to decompose and produce gas. The synthesis of lithium nickel oxide is difficult and has poor cycle stability. The temperature of ternary lithium batteries rises sharply after high-power charging and discharging, and the oxygen released at high temperature is extremely easy to burn, with poor safety and poor high temperature resistance. Lithium iron phosphate (LFP) positive electrode materials have become the main research object of power batteries for new energy vehicles due to their excellent cycle stability and safety performance, low price and superior environmental performance.
[0003] When new energy vehicles are driving or parked at high temperatures, the temperature inside the vehicle can reach 70°C or even higher. Therefore, high temperature conditions place very high demands on the performance and service life of lithium batteries. In order to meet the requirements of high-power charging and discharging performance, high-power power batteries for start-stop power supplies require the use of nano-sized positive electrode active materials. Nano-sized positive electrode active materials have a large specific surface area and many surface reaction active sites, which will cause a large number of side reactions with the electrolyte, affecting the battery storage life and safety.
[0004] CN113422049A discloses a lithium iron phosphate positive electrode sheet and a preparation method and application thereof. The preparation method comprises the following steps: (1) mixing a lithium iron phosphate raw material A with a D50 of 450 to 1000 nm and a lithium iron phosphate raw material B with a D50 of 50 to 150 nm in a mass ratio of (4 to 6): (6 to 4) to obtain a mixed lithium iron phosphate; (2) taking the mixed lithium iron phosphate obtained in step (1), mixing it with a conductive agent and a solvent for a second time, and adding a binder for a third time to obtain a slurry; (3) coating the slurry obtained in step (2) on the surface of a current collector, and obtaining the lithium iron phosphate positive electrode sheet by cold pressing.
[0005] CN113451548A discloses a lithium iron phosphate positive electrode sheet and a preparation method, and a lithium iron phosphate lithium-ion battery. The lithium iron phosphate positive electrode sheet contains lithium iron phosphate particles. Among the lithium iron phosphate particles, in terms of the number of particles, lithium iron phosphate particles with a particle size in the range of 50-500nm account for 70-90%, lithium iron phosphate particles with a particle size greater than 500nm and less than 1000nm account for 5-20%, and lithium iron phosphate particles with a particle size in the range of 1-10μm account for 2-10%.
[0006] The above schemes all prepare positive electrode plates by simply doping lithium iron phosphate particles of different particle sizes, but the compaction density of the positive electrode plates obtained is too large, and the high-temperature storage performance of the obtained battery is poor. Summary of the invention
[0007] The purpose of the present invention is to provide a positive electrode plate and a preparation method and application thereof. The positive electrode plate of the present invention adopts a reasonable combination of lithium iron phosphate particles with different particle sizes and compaction densities, which can significantly improve the high-temperature storage performance of the material, thereby improving the high-temperature storage performance of lithium-ion batteries.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a positive electrode sheet, the positive electrode sheet comprising a current collector and a positive electrode active material layer disposed on the surface of the current collector, the positive electrode active material layer comprising a first lithium iron phosphate particle LFP s And the second lithium iron phosphate particles LFP b , the first lithium iron phosphate particles LFP s And the second lithium iron phosphate particles LFP b The median particle size and compacted density satisfy the relationship 0.97≤D s 50 / D b 50+PD s / PD b ≤1.76, where D s 50 is the first lithium iron phosphate particle LFP s The median particle size, D b 50 is the second lithium iron phosphate particle LFP b The median particle size, PD s The first lithium iron phosphate particle LFP s The compacted density, PD b The second lithium iron phosphate particle LFP b compacted density.
[0010] The present invention uses nano-sized and uniform-sized lithium iron phosphate positive electrode material mixed with a certain proportion of micron-sized and submicron-sized large-particle lithium iron phosphate as the positive electrode active material, and reasonably designs the relationship between the median particle size and the compaction density of the positive electrode active material to ensure a reasonable ratio between the compaction density and the average particle size of the positive electrode active material, thereby obtaining a battery with excellent rate performance and long storage life.
[0011] Preferably, the first lithium iron phosphate particles LFP s The median particle size D s 50 is 0.4 to 0.9 μm, for example, 0.4 μm, 0.5 μm, 0.6 μm, 0.8 μm or 0.9 μm, etc.
[0012] Preferably, the second lithium iron phosphate particles LFP b The median particle size D b 50 is 1.0 to 1.7 μm, for example, 1 μm, 1.2 μm, 1.3 μm, 1.6 μm or 1.7 μm, etc.
[0013] Preferably, the first lithium iron phosphate particles LFP s The compacted density PD s 1.85~2.00g / cm 3 , for example: 1.85g / cm 3 , 1.9g / cm 3 , 1.95g / cm 3 、1.98g / cm 3 or 2g / cm 3 wait.
[0014] Preferably, the second lithium iron phosphate particles LFP b The compacted density PD b 2.3~2.6g / cm 3 , for example: 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 , 2.58g / cm 3 or 2.6 g / cm 3 wait.
[0015] Preferably, the first lithium iron phosphate particles LFP s And the second lithium iron phosphate particles LFP b The mass ratio is (7.5-9):(1-2.5), for example: 7.5:2.5, 8:2, 8.2:1.8, 8.5:1.5 or 9:1, etc.
[0016] In a second aspect, the present invention provides a method for preparing the positive electrode sheet as described in the first aspect, the preparation method comprising the following steps:
[0017] (1) mixing a positive electrode active material, a first conductive agent and a solvent, adding a second conductive agent after a first step of stirring, and obtaining a mixed solution after a second step of stirring;
[0018] (2) mixing a binder and a solvent to obtain a positive electrode glue solution, mixing the positive electrode glue solution and the mixed solution obtained in step (1) and stirring in three steps, adding a solvent to adjust the slurry viscosity and stirring in four steps to obtain a positive electrode slurry;
[0019] (3) The positive electrode slurry is coated on the surface of the positive electrode current collector to obtain a positive electrode sheet.
[0020] Preferably, the mass ratio of the positive electrode active material, the first conductive agent, the second conductive agent and the binder is (92-98):(1-3):(0.2-0.8):(2-3), for example: 92:3:0.6:3, 94:1.5:0.8:2.5, 95:2:0.5:2.5, 96:2.5:0.5:3 or 98:2:0.4:2.5, etc.
[0021] Preferably, the first conductive agent includes conductive carbon black SP.
[0022] Preferably, the one-step stirring includes primary stirring and secondary stirring.
[0023] Preferably, the revolution speed of the stirring is 24-26 rpm, for example, 24 rpm, 24.5 rpm, 25 rpm, 25.5 rpm or 26 rpm.
[0024] Preferably, the dispersion speed of the primary stirring is 450-550 rpm, for example, 450 rpm, 480 rpm, 500 rpm, 520 rpm or 550 rpm.
[0025] Preferably, the stirring time is 8 to 12 minutes, for example, 8 minutes, 9 minutes, 10 minutes, 11 minutes or 12 minutes.
[0026] Preferably, the revolution speed of the secondary stirring is 24-26 rpm, for example, 24 rpm, 24.5 rpm, 25 rpm, 25.5 rpm or 26 rpm.
[0027] Preferably, the dispersion speed of the secondary stirring is 950-1050 rpm, for example, 950 rpm, 980 rpm, 1000 rpm, 1020 rpm or 1050 rpm.
[0028] Preferably, the secondary stirring time is 80 to 100 min, for example, 80 min, 85 min, 90 min, 95 min or 100 min.
[0029] Preferably, the second conductive agent comprises carbon nanotubes.
[0030] Preferably, the revolution speed of the two-step stirring is 24-26 rpm, for example, 24 rpm, 24.5 rpm, 25 rpm, 25.5 rpm or 26 rpm.
[0031] Preferably, the dispersion speed of the two-step stirring is 950-1050 rpm, for example, 950 rpm, 980 rpm, 1000 rpm, 1020 rpm or 1050 rpm.
[0032] Preferably, the vacuum degree of the two-step stirring is 0.06-0.1 kPa, for example, 0.06 kPa, 0.07 kPa, 0.08 kPa, 0.09 kPa or 0.1 kPa.
[0033] Preferably, the second-step stirring time is 50 to 70 min, for example, 50 min, 55 min, 60 min, 65 min or 70 min.
[0034] Preferably, the binder comprises polyvinylidene fluoride.
[0035] Preferably, the revolution speed of the three-step stirring is 24-26 rpm, for example: 24 rpm, 24.5 rpm, 25 rpm, 25.5 rpm or 26 rpm.
[0036] Preferably, the dispersion speed of the three-step stirring is 2450-2550 rpm, for example: 2450 rpm, 2480 rpm, 2500 rpm, 2520 rpm or 2550 rpm.
[0037] Preferably, the vacuum degree of the three-step stirring is 0.06-0.1 kPa, for example, 0.06 kPa, 0.07 kPa, 0.08 kPa, 0.09 kPa or 0.1 kPa.
[0038] Preferably, the three-step stirring time is 80 to 90 min, for example, 80 min, 82 min, 85 min, 88 min or 90 min.
[0039] Preferably, the revolution speed of the four-step stirring is 14-16 rpm, for example: 14 rpm, 14.5 rpm, 15 rpm, 15.5 rpm or 16 rpm.
[0040] Preferably, the dispersion speed of the four-step stirring is 450-550 rpm, for example: 450 rpm, 480 rpm, 500 rpm, 520 rpm or 550 rpm, etc.
[0041] Preferably, the vacuum degree of the four-step stirring is 0.06-0.1 kPa, for example, 0.06 kPa, 0.07 kPa, 0.08 kPa, 0.09 kPa or 0.1 kPa.
[0042] Preferably, the stirring time of the four steps is 20 to 40 minutes.
[0043] Preferably, the viscosity of the positive electrode slurry is 15000-25000 mPa·s.
[0044] Preferably, the fineness of the positive electrode slurry is ≤15 μm.
[0045] In a third aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet as described in the first aspect.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] (1) The present invention reasonably designs the positive electrode active material so that the compaction density and average particle size of the positive electrode active material satisfy a certain relationship, thereby obtaining a battery with excellent rate performance and long storage life.
[0048] (2) The capacity retention rate of the battery made of the positive electrode sheet of the present invention can reach more than 85.9% after storage at 60°C for 30 days, and the capacity retention rate of the battery made of the positive electrode sheet of the present invention can reach more than 97.6% after discharge at 25°C and 5C, and the iron dissolution can reach less than 213 ppm. DETAILED DESCRIPTION
[0049] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0050] Unless otherwise specified, all the ratios in the Examples and Comparative Examples of the present invention are by mass.
[0051] Example 1
[0052] This embodiment provides a positive electrode sheet, wherein LFP (LFP s :LFP b =9.5:0.5, D s 50 = 0.65 μm, D b 50=1.10μm,PD s =1.98g / cm 3 , P.D. b=2.55g / cm 3 , D s 50 / D b 50+PD s / PD b =1.366):SP:CNT:PVDF=95.0:2.0:0.5:2.5, the preparation method of the positive electrode sheet comprises the following steps:
[0053] (1) Add LiFePO4, SP, and NMP, rotate at 25 rpm, disperse at 500 rpm, stir for 10 min, then rotate at 25 rpm, disperse at 1000 rpm, stir at 45°C for 90 min, add conductive agent CNT slurry, rotate at 25 rpm, disperse at 1000 rpm, vacuum at 0.080 KPa, stir at 45°C for 60 min, and obtain a mixed solution;
[0054] (2) PVDF and solvent are mixed to obtain a positive electrode glue solution with a solid content of 8%, and the positive electrode glue solution is mixed with the mixed solution obtained in step (1), and the mixture is rotated at 25 rpm, dispersed at 2500 rpm, and vacuumed at 0.080 KPa. The mixture is stirred at 45° C. for 90 min, and NMP is added to adjust the viscosity of the slurry. The mixture is slowly stirred at 15 rpm, dispersed at 500 rpm, and vacuumed at 0.080 KPa. The mixture is stirred for 0.5 h to cool down, and the viscosity of the positive electrode discharge is ensured to be 20000 mPa·s, and the fineness is ≤15 μm. The deposited materials on the wall of the stirring cylinder and the stirring rod are scraped in time at each step.
[0055] (3) The positive electrode slurry is coated on the surface of the positive electrode current collector to obtain a positive electrode sheet.
[0056] Example 2
[0057] This embodiment provides a positive electrode sheet, wherein LFP (LFP s :LFP b =9:1, D s 50 = 0.68 μm, D b 50=1.2μm,PD s =1.95g / cm 3 , P.D. b =2.52g / cm 3 , D s 50 / D b 50+PD s / PD b =1.34):SP:CNT:PVDF=95.0:2.0:0.5:2.5, the preparation method of the positive electrode sheet comprises the following steps:
[0058] (1) Add LiFePO4, SP, and NMP, rotate at 24 rpm, disperse at 510 rpm, stir for 10 min, then rotate at 24 rpm, disperse at 1020 rpm, stir at 45°C for 90 min, add conductive agent CNT slurry, rotate at 24 rpm, disperse at 1020 rpm, vacuum at 0.080 KPa, stir at 45°C for 60 min, and obtain a mixed solution;
[0059] (2) PVDF and solvent are mixed to obtain a positive electrode glue solution with a solid content of 8%, and the positive electrode glue solution is mixed with the mixed solution obtained in step (1), and the mixture is rotated at 24 rpm, dispersed at 2520 rpm, and vacuumed at 0.080 KPa. The mixture is stirred at 45° C. for 90 min, and NMP is added to adjust the viscosity of the slurry. The mixture is slowly stirred and rotated at 15 rpm, dispersed at 500 rpm, and vacuumed at 0.080 KPa. The mixture is stirred for 0.5 h to cool down, and the viscosity of the positive electrode discharge is ensured to be 20000 mPa·s, and the fineness is ≤15 μm. The deposited materials on the wall of the stirring cylinder and the stirring rod are scraped in time at each step.
[0060] (3) The positive electrode slurry is coated on the surface of the positive electrode current collector to obtain a positive electrode sheet.
[0061] Example 3
[0062] The difference between this embodiment and embodiment 1 is that LFP s :LFP b =8.5:1.5, other conditions and parameters are exactly the same as those in Example 1.
[0063] Example 4
[0064] The difference between this embodiment and embodiment 1 is that LFP s :LFP b =8:2, and other conditions and parameters are exactly the same as those in Example 1.
[0065] Example 5
[0066] The difference between this embodiment and embodiment 1 is that LFP s :LFP b =7.5:2.5, other conditions and parameters are exactly the same as those in Example 1.
[0067] Comparative Example 1
[0068] The difference between this comparative example and Example 1 is that only LFP is used. s As the positive electrode active material, other conditions and parameters are exactly the same as those in Example 1.
[0069] Comparative Example 2
[0070] The difference between this comparative example and Example 1 is that only LFP is used. bAs the positive electrode active material, other conditions and parameters are exactly the same as those in Example 1.
[0071] Comparative Example 3
[0072] The difference between this comparative example and Example 1 is that D s 50 = 1.2 μm, D b 50=0.9μm,PD s =2.1g / cm 3 , P.D. b =2.2g / cm 3 , D s 50 / D b 50+PD s / PD b =2.28, and other conditions and parameters are exactly the same as those in Example 1.
[0073] Comparative Example 4
[0074] The difference between this comparative example and Example 1 is that D s 50 = 0.3 μm, D b 50=2μm,PD s =1.8g / cm 3 , P.D. b =2.65g / cm 3 , D s 50 / D b 50+PD s / PD b =0.83, and other conditions and parameters are exactly the same as those in Example 1.
[0075] Performance Test:
[0076] Take graphite: SP: CMC: SBR = 95.5: 1.5: 1.2: 1.8. The solid content of the negative electrode glue is 1.3%. The first step is to add graphite and SP dry mix, rotate at 20 ± 1r / min, disperse at 1000 ± 50r / min, and stir for 1h; the second step is to add 50% negative electrode slurry, rotate at 20 ± 1r / min, disperse at 1000 ± 50r / min, and stir for 1.5h; the third step is to add another 50% negative electrode glue, rotate at 25 ± 1r / min, disperse at 2000 ± 50r / min, vacuum degree 0.085KPa, and stir for 1h; the fourth step is the viscosity adjustment step, adding deionized water to adjust the slurry viscosity; the fifth step is to add water-based dispersant SBR, rotate at 25 ± 1r / min, disperse at 800 ± 50r / min, vacuum degree 0.085KPa, and stir for 1h. Ensure that the negative electrode material has a viscosity of 4000±1500mPa·s and a fineness of ≤20μm, and that the deposited material on the mixing cylinder wall and the mixing rod is scraped off in time at each step. The negative electrode sheet is obtained by sieving, coating, cold pressing, and cutting;
[0077] Take the positive electrode plates obtained in Examples 1-5 and Comparative Examples 1-4, the electrolyte is conventional lithium iron phosphate, the lithium salt is lithium hexafluorophosphate LiPF6, the concentration is 1.00 mol, the solvent system is ethylene carbonate EC: propylene carbonate PC: ethyl methyl carbonate EMC: fluorobenzene FB = 30:5:62:3, the additives vinyl chloride VC are 3.0% and methylene disulfonate MMDS are 0.3%, and the separator is a base film of 25 μm;
[0078] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound into a square bare cell, loaded with aluminum plastic film, and then baked at 80°C to remove water, and then injected with electrolyte, sealed, and after standing, hot and cold pressing, formation, clamping, capacity division and other processes, a lithium-ion battery is obtained. The performance of the obtained battery is tested, and the test results are shown in Table 1:
[0079] Table 1
[0080]
[0081] As can be seen from Table 1, from Examples 1-5, the capacity retention rate of the battery made of the positive electrode sheet of the present invention after storage for 30 days at 60°C can reach more than 85.9%, the capacity retention rate of the discharge at 25°C 5C can reach more than 97.6%, and the iron dissolution can reach less than 213 ppm.
[0082] From the comparison between Example 1 and Comparative Examples 1-2, it can be seen that the present invention can improve the storage and cycle performance of the positive electrode sheet while ensuring the battery discharge efficiency by doping a nano-sized and uniform-sized lithium iron phosphate positive electrode material with a certain proportion of micron-sized and submicron-sized large-particle lithium iron phosphate as the positive electrode active material.
[0083] From the comparison between Example 1 and Comparative Examples 3-4, it can be seen that the present invention reasonably designs the positive electrode active material so that the compaction density and the average particle size of the positive electrode active material satisfy a certain relationship, thereby obtaining a battery with excellent rate performance and long storage life.
[0084] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode plate includes a current collector and a positive electrode active material layer disposed on the surface of the current collector, wherein the positive electrode active material layer includes a first lithium iron phosphate particle LFP s And the second lithium iron phosphate particles LFP b , the first lithium iron phosphate particles LFP s And the second lithium iron phosphate particles LFP b The median particle size and compacted density satisfy the relationship 1.34≤D s 50 / D b 50+PD s / PD b ≤1.76, where D s 50 is the first lithium iron phosphate particle LFP s The median particle size, D b 50 is the second lithium iron phosphate particle LFP b The median particle size, PD s The first lithium iron phosphate particle LFP s The compacted density, PD b The second lithium iron phosphate particle LFP b The compacted density; The median particle size D of the first lithium iron phosphate particles LFPs is s 50: 0.4-0.9 μm; The median particle size D of the second lithium iron phosphate particle LFPb is b 50: 1.0~1.7μm; The first lithium iron phosphate particles LFP s The compacted density PD s 1.85~2.00g / cm 3 ; The second lithium iron phosphate particles LFP b The compacted density PD b 2.30~2.60g / cm 3 ; The first lithium iron phosphate particles LFP s And the second lithium iron phosphate particles LFP b The mass ratio is (7.5~9):(1~2.5).
2. A method for preparing a positive electrode sheet as claimed in claim 1, characterized in that: The preparation method comprises the following steps: (1) mixing a positive electrode active material, a first conductive agent and a solvent, adding a second conductive agent after a first step of stirring, and obtaining a mixed solution after a second step of stirring; (2) mixing a binder and a solvent to obtain a positive electrode glue solution, mixing the positive electrode glue solution and the mixed solution obtained in step (1) and stirring in three steps, adding a solvent to adjust the slurry viscosity and stirring in four steps to obtain a positive electrode slurry; (3) The positive electrode slurry is coated on the surface of the positive electrode current collector to obtain a positive electrode sheet.
3. The preparation method according to claim 2, characterized in that: The mass ratio of the positive electrode active material, the first conductive agent, the second conductive agent and the binder is (92-98):(1-3):(0.2-0.8):(2-3).
4. The preparation method according to claim 2, characterized in that: The first conductive agent includes conductive carbon black SP.
5. The preparation method according to claim 2, characterized in that: The one-step stirring includes primary stirring and secondary stirring.
6. The preparation method according to claim 5, characterized in that: The revolution speed of the primary stirring is 24-26 rpm.
7. The preparation method according to claim 5, characterized in that: The dispersion speed of the primary stirring is 450-550 rpm.
8. The preparation method according to claim 5, characterized in that: The time of the first stirring is 8 to 12 minutes.
9. The preparation method according to claim 5, characterized in that: The revolution speed of the secondary stirring is 24-26 rpm.
10. The preparation method according to claim 5, characterized in that: The dispersion speed of the secondary stirring is 950-1050 rpm.
11. The preparation method according to claim 5, characterized in that: The secondary stirring time is 80 to 100 minutes.
12. The preparation method according to claim 2, characterized in that: The second conductive agent includes carbon nanotubes.
13. The preparation method according to claim 2, characterized in that: The revolution speed of the two-step stirring is 24-26 rpm.
14. The preparation method according to claim 2, characterized in that: The dispersion speed of the two-step stirring is 950-1050 rpm.
15. The preparation method according to claim 2, characterized in that: The vacuum degree of the two-step stirring is 0.06-0.1 kPa.
16. The preparation method according to claim 2, characterized in that: The time of the two-step stirring is 50 to 70 minutes.
17. The preparation method according to claim 2, characterized in that: The binder includes polyvinylidene fluoride.
18. The preparation method according to claim 2, characterized in that: The revolution speed of the three-step stirring is 24-26 rpm.
19. The preparation method according to claim 2, characterized in that: The dispersion speed of the three-step stirring is 2450-2550 rpm.
20. The preparation method according to claim 2, characterized in that: The vacuum degree of the three-step stirring is 0.06-0.1 kPa.
21. The preparation method according to claim 2, characterized in that: The three-step stirring time is 80 to 90 minutes.
22. The preparation method according to claim 2, characterized in that: The revolution speed of the four-step stirring is 14-16 rpm.
23. The preparation method according to claim 2, characterized in that: The dispersion speed of the four-step stirring is 450-550 rpm.
24. The preparation method according to claim 2, characterized in that: The vacuum degree of the four-step stirring is 0.06-0.1 kPa.
25. The preparation method according to claim 2, characterized in that: The stirring time of the four steps is 20 to 40 minutes.
26. The preparation method according to claim 2, characterized in that: The viscosity of the positive electrode slurry is 15000-25000 mPa·s.
27. The preparation method according to claim 2, characterized in that: The fineness of the positive electrode slurry is ≤15 μm.
28. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as claimed in claim 1.
Citation Information
Patent Citations
Lithium iron phosphate positive pole piece and preparation method and application thereof
CN113422049A
Lithium iron phosphate positive plate, preparation method and lithium iron phosphate lithium ion battery
CN113451548A
Lithium iron manganese phosphate composite, preparation method therefor, and lithium-ion battery positive electrode
WO2022111186A1